High‐resolution melt analysis for the detection of skin/sweat via DNA methylation. Issue 3 (28th December 2022) - Fernandez‐Tejero, Nicole; Gauthier, Quentin; Cho, Sohee; McCord, Bruce R.
Abstract: The determination of tissue type is important when reconstructing a crime scene as skin cells may indicate innocent contact, whereas other types of cells, such as blood and semen, may indicate foul play. Up to now, there has been no specific DNA methylation‐based marker to distinguish skin cell DNA from other body fluids. The goal of this study is to develop a DNA methylation‐based assay to detect and identify skin cells collected at forensic crime scenes for use in DNA typing. For this reason, we have utilized a DNA methylation chip array‐based genome‐wide association study to identify skin‐specific DNA methylation markers. DNA obtained from skin along with other body fluids, such as semen, saliva, blood, and vaginal epithelia, were tested using five genes that were identified as sites for potential new epigenetic skin markers. Samples were collected, bisulfite converted, and subjected to real‐time polymerase chain reaction (PCR) with high‐resolution melt analysis. In our studies, when using WDR11, PON2, and NHSL1 assays with bisulfite‐modified PCR, skin/sweat amplicons melted at lower temperatures compared to blood, saliva, semen, and vaginal epithelia. One‐way analysis of variance demonstrates that these three skin/sweat markers are significantly different when compared with other body fluids ( p  < 0.05). These results demonstrate that high‐resolution melt analysis is a promising technology to detect and identify skin/sweat DNA from other body fluids.